2014
DOI: 10.1038/nature13234
|View full text |Cite
|
Sign up to set email alerts
|

A Ctf4 trimer couples the CMG helicase to DNA polymerase α in the eukaryotic replisome

Abstract: Efficient duplication of the genome requires the concerted action of helicase and DNA polymerases at replication forks1, to avoid stalling of the replication machinery and consequent genomic instability2-4. In eukaryotes, the physical coupling between helicase and DNA polymerases remains poorly understood. Here we define the molecular mechanism by which the yeast Ctf4 protein links the Cdc45-MCM-GINS (CMG) DNA helicase to DNA polymerase α (Pol α) within the replisome. We use X-ray crystallography and electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
274
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 201 publications
(291 citation statements)
references
References 46 publications
17
274
0
Order By: Relevance
“…Yeast Ctf4 forms a functional trimer that acts as a multivalent interface between the MCM2-7 helicase-associated GINS complex and DNA-polα during replication (29). This interaction is mediated through specific recognition of a peptide motif found in DNA-polα and Sld5 with the α-helical fold of Ctf4 (29,34,35). We confirmed an interaction between plant EOL1 and SLD5 (Fig.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Yeast Ctf4 forms a functional trimer that acts as a multivalent interface between the MCM2-7 helicase-associated GINS complex and DNA-polα during replication (29). This interaction is mediated through specific recognition of a peptide motif found in DNA-polα and Sld5 with the α-helical fold of Ctf4 (29,34,35). We confirmed an interaction between plant EOL1 and SLD5 (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…This domain structure is found in yeast Ctf4 and metazoan Actinodin 1 (AND1)/ WD-and-High-mobility-group-domain protein 1 (WDHD1), components of the nuclear DNA replisome (34,35). A recently solved crystal structure of Ctf4 showed that DUF3639 is part of a novel WD40-related domain that forms a β-propeller with six blades (β-6-prop), forming a stable trimer (29). The carboxyl-terminal end of Ctf4 extends as α-helical fold that can interact with a motif found in both DNA-Polα and Sld5 (29).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations